Contraventions of MPA regulations by the South African demersal trawl fisheries: Evidence from loss and damage of scientific instruments - Fannie W. Shabangu; Trevor A. Branch; Kuhle Hlati; Flore Samaran; Imtiyaaz Malick; Sean T. Fennessy; Bernadine I. Everett; Marcel A. van den Berg; Dawit Yemane (Regional Studies in Marine Science, 2025)

Separating Historical Catches Among Pygmy Blue Whale Populations Using Recent Song Detections - Trevor A. Branch; Cole C. Monnahan; Emmanuelle C. Leroy; Fannie W. Shabangu; Ana Širović; Salvatore Cerchio; Suaad Al Harthi; Cherry Allison; Naysa Balcázar Cabrera; Dawn R. Barlow; Susannah V. Calderan; Michael C. Double; et al. (Marine Mammal Science, 2025)
In the Southern Hemisphere and northern Indian Ocean, there are at least five populations of pygmy blue whales, Balaenoptera musculus brevicauda , residing in the Northwest Indian Ocean (NWIO, Oman), central Indian Ocean (CIO, Sri Lanka), Southwest Indian Ocean (SWIO, Madagascar to Subantarctic), Southeast Indian Ocean (SEIO, Australia to Indonesia), and Southwest Pacific Ocean (SWPO, New Zealand). Each population produces a distinctive repeated song, but none have population assessments or reliable measures of historical whaling pressure. Here we created pygmy blue whale catch time series by removing Antarctic blue whale catches using length data and then fitting generalized additive models (based on latitude, longitude, and month) to contemporary song data (largely from 1995 to 2023) to allocate historical catches to the five populations. Most pygmy blue whale catches (97% of 12,207) were taken by Japanese and Soviet operations during 1959/1960 to 1971/1972, with the highest totals taken from the SWIO (6514), SEIO (2593), and CIO (2023), and lower catches from the NWIO (549) and SWPO (528). The resulting predicted annual catch assignments provide the first indication of the magnitude of whaling pressure on each population and are a key step toward assessing the status of these five pygmy blue whale populations.

Sea Ice as a Driver of Fin Whale (Balaenoptera physalus) 20 Hz Acoustic Presence in Eastern Antarctic Waters - Meghan G. Aulich; Agustin M. De Wysiecki; Brian S. Miller; Flore Samaran; Robert D. McCauley; Benjamin J. Saunders; Cristina D. S. Tollefsen; Christine Erbe (Journal of Marine Science and Engineering, 2025)
The environmental drivers of fin whale (Balaenoptera physalus) acoustic presence in Eastern Antarctic waters were investigated based on passive acoustic recordings from four sites, 2013–2019. Fin whale 20 Hz pulses were detected from late austral summer to early winter. Daily values of sea-ice concentration (SIC) were compared with the number of days with fin whale 20 Hz acoustic presence using a generalized additive model approach. At the Southern Kerguelen Plateau, Casey, and Dumont d’Urville sites, SIC correlated with fin whale calling activity, but less so at the Prydz site. Changes in SIC between sites resulted in variation in acoustic presence: Earlier sea-ice formation at Dumont d’Urville resulted in less acoustic presence in comparison to the Southern Kerguelen Plateau, where sea ice formed later in the season. Interannual variability in SIC impacted yearly acoustic presence, with a later onset of high SIC resulting in greater acoustic presence and later departure (migration timing) of the animals. Identifying the environmental drivers of fin whale presence is key to informing how this migratory species may be affected by environmental variability resulting from climate change.

Passive acoustic monitoring for assessing marine mammals population in European waters: Workshop conclusions and perspectives - Mathilde Michel; Benjamin Guichard; Julie Béesau; Flore Samaran (Marine Policy, 2024)

Long‐term acoustic monitoring of nonstereotyped blue whale calls in the southern Indian Ocean - Maëlle Torterotot; Flore Samaran; Jean‐Yves Royer (Marine Mammal Science, 2023)
Monitoring the presence of blue whale ( Balaenoptera musculus ssp.) stereotyped calls has been a widely used method to assess the different populations' distribution worldwide. All blue whale populations also produce nonstereotyped vocalizations, or D‐calls. Here, we monitored the presence of D‐calls in long‐term records from a large hydrophone array located in the open southern Indian Ocean, using an automated detection method and manual validation of the detections. D‐calls were detected at all sites of the array, which extends from 24°S to 56°S, but the majority of them were detected at the two southernmost sites. We observed a latitudinal shift in their seasonal occurrence, with more D‐calls in the north during austral autumn and winter and more in the south during austral spring. The geographical occurrence of D‐calls compared to that of songs indicates that blue whale acoustic behavior switches from a song‐intensive and sparse‐D‐call emission in the north to song‐moderate and more intensive D‐call emissions in the south. These findings support the hypothesis that both call types are used for different purposes, as D‐calls are mainly detected around foraging grounds and songs in wintering grounds. Monitoring both call types might therefore be a relevant acoustic indicator of blue whale behavior.

Seasonal Distribution of the Fin Whale (Balaenoptera physalus) in Antarctic and Australian Waters Based on Passive Acoustics - Meghan G. Aulich; Robert D. McCauley; Brian S. Miller; Flore Samaran; Giacomo Giorli; Benjamin J. Saunders; Christine Erbe (Frontiers in Marine Science, 2022)
The fin whale is listed as globally vulnerable, with ongoing threats to their population, yet little is known about the distribution and movements of the Southern Hemisphere sub-species, Balaenoptera physalus quoyi . This study assesses fin whale distribution in the Southern Hemisphere analysing acoustic recordings from 15 locations in Antarctic and Australian waters from 2002 to 2019. A seasonal acoustic presence of fin whales in Antarctic waters from late austral summer to autumn (February to June) with long-term, consistent annual usage areas was identified at the Southern Kerguelen Plateau and Dumont d’Urville sites. In comparison, limited vocal presence of fin whales was observed at the Casey site. In Australian waters, fin whales were seasonally present from austral autumn to mid-spring (May to October) on east and west coasts, with a decadal pattern of acoustic presence observed at Cape Leeuwin, WA. Two migratory pathways are identified, from the Indian sector of Antarctica to the west coast of Australia and from the Pacific sector of Antarctica to the east coast of Australia. The identified seasonal distributions and migratory pathways provide valuable information to aid in monitoring the recovery of this vulnerable sub-species. We suggest the identified distribution and dispersal from the Southern Kerguelen Plateau and Dumont d’Urville sites to the west and east coasts of Australia respectively, as well as the spatial separation between Antarctic sites, provide preliminary evidence of separate sub-populations of the Southern Hemisphere sub-species of fin whale.

Passive acoustic monitoring reveals feeding attempts at close range from soaking demersal longlines by two killer whale ecotypes - Gaëtan Richard; Julien Bonnel; Julie Beesau; Eva Calvo; Fabio Cassiano; Maéva Dramet; Aziliz Glaziou; Kinga Korycka; Christophe Guinet; Flore Samaran (Marine Mammal Science, 2022)
Odontocetes depredating fish caught on longlines is a serious socio‐economic and conservation issue. A good understanding of the underwater depredation behavior by odontocetes is therefore required. Historically, depredation on demersal longlines has always been assumed to occur during the hauling phase. In this study, we have focused on the depredation behavior of two ecotypes of killer whales, Orcinus orca , (Crozet and Type D) from demersal longlines around the Crozet Archipelago (Southern Indian Ocean) using passive acoustic monitoring. We assessed 74 hr of killer whale acoustic presence out of 1,233 hr of recordings. Data were obtained from 29 hydrophone deployments from five fishing vessels between February and March 2018. We monitored killer whale buzzing activity (i.e., echolocation signals) as a proxy for feeding attempts around soaking longlines. These recordings revealed that the two ecotypes were feeding at close range from soaking longlines, even when fishing vessels were not present. Our results suggest that both killer whale ecotypes are likely to depredate soaking longlines, which would imply an underestimation of their depredation rates. The implication of underestimating depredation rates is inaccurate accounting for fish mortality in fisheries' stock assessments.

Antarctic blue whales ( Balaenoptera musculus intermedia ) recorded at the Equator in the Atlantic Ocean - Flore Samaran; Adrien Berne; Emmanuelle C. Leroy; Sérgio Moreira; Kathleen M. Stafford; Marcia Maia; Jean‐Yves Royer (Marine Mammal Science, 2019)